Architecture from the Ouija Board: Louis Kahn’s Roosevelt memorials and the posthumous monuments of modernism - Sully, Nicole (Fabrications, 2019)
In 2012, the USA received its newest Presidential memorial. Four Freedoms Park, designed by Louis Kahn and situated on Roosevelt Island in New York, honours Franklin Delano Roosevelt, the country’s 32nd President. Completed almost seven decades after the President’s death, and four decades after the death of its architect, the project forms one of a growing number of architectural works that can be regarded as what this paper terms “posthumous monuments of modernism,” being projects that have been constructed not from the desk of the architect, but rather from their historical archive. This paper considers the problem of the posthumous monument in relation to the specific case study of Louis Kahn’s Roosevelt Memorial. It will first offer an account of the emergence of this memorial, and then, through this work, consider the ethical, philosophical, and historical implications of posthumous architecture.